PEMBUATAN SEDIAAN MINYAK GOSOK DARI BAHAN KELAPA (Cocos nucifera L.), SERAI (Cymbopogon citratus DC.) dan DAUN DEWA (Gynura segetum L.) dengan METODE PENGENDAPAN TRADISIONAL - Tanka, Rickson; Andriani, Susi; Helmiawati, Yusi (Sekolah Tinggi Ilmu Kesehatan Holistik, 2017)
Backgroud: Plant is a biodiversity that all around us, whether it was growing wild and cultivated intentionally. Herbs have been used as a medicinal plant, although its use spread by generations. The aim: This research aim to provide the herbs that can be used by the community for the treatment of colds. Method: This research is a descriptive study developed by the community for generations, conducted interviews to the public regarding the efficacy of purecoconut oil (virgin coconut oil) with a mixture of lemongrass (Cymbopogon citratus DC.) and god leaf (Gynura segetum L.) for currycomb. In this reasearchmade preparations ointment of coconut (Cocos nucifera L.) which become extract virgin coconut oil with lemongrass and god leaf as currycomb through thedeposition process for four days using water-soluble. Ointments made with the coconut two kilograms of shredded added to water as much as one liter of twotimes juice, in the can of coconut milk as much as 1800 ml and filtered coconut milk, settling for three days to produce virgin coconut oil 200 cc, pure coconut oil (VCO) add lemongrass (Cymbopogon citratus DC.) of 20 grams and leaves god (Gynura segetum L.) 20 grams chopped settling for one day then filtered andgenerate ointment five bottles with each weight 20 cc. Result: Results showing test organoleptic dosage for three weeks are not changes the shape, color, taste and smell of mold growth. Conclusion: Research is successful prepare an ointment hold for three weeks.